Pondok Pesantren Sebagai Model Pendidikan Islam Indonesia - Pauzan Septiawan (Journal of Islamic Education Policy, 2018)
Abstract., Today's education problems are the responsibility of all parties. In terms of implementation and concept, education should be divided and provide a concrete solution for the growth and development of the human resources of Indonesian children. Islamic boarding schools are one of the original educational features based on the Indonesian character. Islamic boarding schools in a long period of time have proven that education is an effort to develop humanity as a whole, starting from morals, intellectuals and skills and provisions for students in navigating life. Educational patterns that use a boarding school system are able to provide comprehensive learning. The concept of Islamic boarding school education makes learning not only limited to classrooms and books, it covers all dimensions of life in the daily activities of students. Morals are cultivated through habitual practice, knowledge is given in every activity that is tightly arranged for a full day. Islamic boarding schools are the legacy of the scholars and the hopes of the founding fathers of the nation. In the end, Islamic boarding schools get attention and become a solution for the world of Islamic education in Indonesia. Keyword; Islamic education, Islamic boarding schools, Islamic Indonesia, character educationAbstraksi., Problematika pendidikan hari ini merupakan tanggung jawab semua pihak. Dari sisi penyelenggaraan serta konsep, pendidikan hendaklah terus berbebnah dan memberikan solusi yang kongkrit bagi tumbuh kembang sumber daya manusia anak Indonesia. Pondok pesantren merupakan salah satu corak pendidikan yang original  yang berbasis pada karakter keindonesiaan. Pondok pesantren dalam kurun masa yang cukup panjang telah membuktikan bahwa pendidikan merupakan sebuah upaya untuk mengembangkan manusia secara keseluruhan, mulai dari akhlak, intelektual maupun keterampilan dan bekal bagi para peserta didik dalam mengarungi kehidupan. Corak pendidikan yang menggunakan sistem boarding school mampu memberikan pembelajaran yang komprehensif. Konsep Pendidikan pondok pesantren menjadikan pembelajaran tidak terbatas pada ruang kelas dan buku semata, tetapi mencakup seluruh dimensi kehidupan dalam aktifitas keseharian para peserta didik. Akhlak dibina melalui pembiasaan laku, pengetahuan diberikan dalam setiap aktifitas-aktiftas yang tersusun dengan ketat selama sehari penuh. Pondok pesantren adalah warisan para ulama dan harapan para pendiri bangsa. Karena itu, pondok pesantren layak mendapatkan perhatian dan menjadi sebauh solusi bagi dunia pendidikan Islam di Indonesia.Keyword; pendidikan Islam, pondok pesantren, Islam Indonesia, pendidikan karakter